Socio-demographic and Clinico-pathological Profile of Cervical Cancer Patients at a Tertiary Care Centre in New Delhi: A Five-Year Retrospective analysis - Shrivastav, Kumar Dron; Taneja, Neha; Das, Ankan Mukherjee; Rana, Shweta; Ranjan, Priya; Singh, Harpreet; Jaggi, Vinita Kumar; Janardhanan, Rajiv (Indian Journal of Community Health, 2021)
Background: Cervical cancer remains a major public health challenge in low and middle-income countries including India. However, if detected early, it is preventable and curable. Objective: The present study aimed to ascertain the sociodemographic and clinical profile of cervical cancer patients visiting a tertiary cancer center. Methodology: A retrospective study was carried out at the Delhi State Cancer Institute, New Delhi. The study population included 136 women who were diagnosed with cervical cancer. A pretested data extraction sheet was used as the study tool for collecting information from the inpatient records. Descriptive analysis and chi-square test were performed and the level of significance was set at p<0.05. Results: A total of 136 cervical cancer patients with mean age of 46 ± 9.85 and mean BMI of 23.78 ± 5.03, were studied retrospectively. About 36.8% of patients were aged between 40-49 years and 57.4% were illiterate. While 40.4% of the patients belonged to FIGO stage II, 27.2% had FIGO stage III cancer. Majority (63.2%) of patients were diagnosed with squamous cell carcinoma (SCC), while the rest were adenocarcinoma (25%) and adenosquamous (11.8%). Clinical stage of cancer was found to be significantly associated with educational status (p=0.03) and dietary practices (p=.007). Conclusion: Our study found higher percentage of women with stage II and III cervical lesions and reaffirms the importance of education and healthy diet in early detection and prevention of cervical cancer. Therefore, it is suggested that accelerated population awareness and screening, incorporating digital innovations including vaccination programs are mandatory.